The wheel of darkness [compact disc, unabridged] - Preston, Douglas J. (Preston, Douglas J. Pendergast novel., 2007)
While on a grand tour Pendergast and Constance learn that a rare and dangerous artifact the monks have been guarding for generations has been mysteriously stolen. Pendergast takes up the search which leads them to the maiden voyage of the Queen Victoria.